Reconceptualizing Motherhood in Modern African Society: An Afrocentric Philosophical Reconstruction of Care, Ubuntu Ethics, and Gender Justice - Michael D Olajide; Olatundun A. Oderinde (The Faculty of Ushuluddin and Humanities, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2026)
This research places the institution of motherhood in modern African society as the main unit of analysis to decipher its shifting cultural values. The purpose of this research is to reconstruct the meaning of motherhood distorted by colonialism and capitalistic modernity through the lens of contemporary philosophy. Using a qualitative method approaching conceptual-analytical analysis, this literature study evaluates the main texts of ethical philosophy and African feminism thought. The findings and novelty of this research prove that the concept of motherhood in Africa is not just an oppressive biological-domestic function, but a relational, ethical, and socially productive institution that provides moral authority for women. This deconstruction gave birth to a new synthesis that sat down as a fair communal responsibility. The scientific contribution of this research is to provide a theoretical blueprint for bridging the tension between radical Western autonomy and traditional communitarianism. Thus, this study offers a robust contextual framework for the formulation of gender justice policies, social sustainability, and the fulfillment of reproductive rights rooted in the local wisdom of modern African societies.